ANALISIS PENGETAHUAN PEDAGOGIK GURU PENDIDIKAN ANAK USIA DINI DI KECAMATAN SEKADAU HILIR KALIMANTAN BARAT - Abdiana, Abdiana; Samawi, Ahmad; Manningtyas, Rosyi Damayani Twinsari (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
Pedagogical competence is one of the important components that a teacher must have. Pedagogic is an expertise or ability that teachers must have in teaching children. Mastery of pedagogical competence of early childhood education teachers can differentiate from other professions and can improve the quality of education quality in Sekadau Hilir District. This study aims to analyze and describe the pedagogical competence of PAUD teachers which includes lesson planning, lesson implementation, and evaluation of children's learning outcomes in Sekadau Hilir District, West Kalimantan. The population of this study was 74 people with a sampling method of probability sampling technique, namely the type of simple random sampling. Then, a sample size of 63 people was obtained, with data collection techniques using a questionnaire. The data analysis method uses an objective description form (BUO), then a percentage calculation is carried out to determine the level of pedagogical competence of PAUD teachers. The results showed that pedagogical competence in Sekadau Hilir Sub-district who scored “Fair” amounted to 41 teachers, the score “Good” amounted to 16 teachers, and the score “Less” amounted to 6 teachers. This shows that the majority of PAUD teachers in Sekadau Hilir Sub-district have sufficient understanding and skills regarding pedagogical knowledge, although there is still room for improvement on lesson planning that needs to be improved.